Improving the Performance of Face Recognition Technique using Brightness Preserving and Contrast Limited Bi-histogram Equalization - Radha, P.; Shanthi, T. (International Journal of Engineering and Technology, 2018)
The Face Recognition technique is one of the highly secured method for incorporating the authentication. Since it uses bio-metric technique which is unique for a person. Face recognition technique involves extraction of feature and train the features for using classifiers for matching. The Extracted features must be precise so that identification becomes perfect.  This paper proposes an innovative method of facial recognition in which facial image is enhanced by the technique Brightness Preserving and Contrast Limited Bi-Histogram Equalization for the image.  Then Features are extracted and those enhanced features extracted are used for Classification using Multi-Class SVM and matching. FERET data base is used. Various parameters such as FAR, FRR, TSR and EER are calculated and compared with the traditional techniques.